2021
DOI: 10.1016/j.stemcr.2021.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated ECM remodeling proteins lead to aberrant osteogenesis of Costello syndrome iPSCs

Abstract: Costello syndrome (CS) is an autosomal dominant disorder caused by mutations in HRAS. Although CS patients have skeletal abnormalities, the role of mutated HRAS in bone development remains unclear. Here, we use CS induced pluripotent stem cells (iPSCs) undergoing osteogenic differentiation to investigate how dysregulation of extracellular matrix (ECM) remodeling proteins contributes to impaired osteogenesis. Although CS patient-derived iPSCs develop normally to produce mesenchymal stem cells (MSCs), the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…Nevertheless, we cannot exclude that CS Hras mutations do not affect their proper function, either by inducing senescence or through other unknown pathomechanisms. Hras is known to affect collagen, extracellular matrix deposition and elastin ( Yamagata et al, 1996 ; Hinek et al, 2000 ; Choi et al, 2021 ), and thus influence bone strength leading to frailty and increased risk for fractures. Therefore, to confirm that Hras does not affect bone strength in mice where bone loss is absent, a functional assay such as 3-point bending test ( Deckard et al, 2017 ; Prodinger et al, 2018 ) would provide valuable information ( Jameson and De Groot, 2010 ; Biver, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, we cannot exclude that CS Hras mutations do not affect their proper function, either by inducing senescence or through other unknown pathomechanisms. Hras is known to affect collagen, extracellular matrix deposition and elastin ( Yamagata et al, 1996 ; Hinek et al, 2000 ; Choi et al, 2021 ), and thus influence bone strength leading to frailty and increased risk for fractures. Therefore, to confirm that Hras does not affect bone strength in mice where bone loss is absent, a functional assay such as 3-point bending test ( Deckard et al, 2017 ; Prodinger et al, 2018 ) would provide valuable information ( Jameson and De Groot, 2010 ; Biver, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, increased RAS signalling due to HRAS G12S mutation impaired osteoblast differentiation and osteogenesis without affecting mesenchymal stem cells. ( Choi et al, 2021 ). In contrast to HRAS, KRAS hyperactivation increases bone mass by increasing mouse osteoblast progenitor cell proliferation via MAPK and AKT pathways without affecting mature osteoblasts ( Ge et al, 2009 ; Li et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al found that hyperactivation of SMAD3 signaling during the osteogenic differentiation of Costello syndrome (CS) MSCs leads to aberrant expression of ECM remodeling proteins such as MMP13, TIMP1, and TIMP2. Specifically, enhanced TIMP1/2 expression induced by hyperactivated SMAD3 signaling impairs the osteogenic development of CS MSCs via inactivation of wnt/β-catenin signaling ( Choi et al, 2021 ). Compared with normal nucleus pulposus (NP) tissues, intervertebral disc degeneration (IDD) samples exhibited higher levels of circular RNA derived from TIMP2 (circ-TIMP2) expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and in vivo studies were performed in NF1, showing a dysregulated activity in cells of the osteoblastic and osteoclastic lineages (Choi et al, 2017; Choi et al, 2021; Kim et al, 2019; Stevenson, Yan, et al, 2011). For example, in vitro studies on induced pluripotent stem cells (iPSCs) from an individual with CFCS that were differentiated into mesenchymal stem cells (MSCs) showed an altered osteogenic differentiation, with reduced activity of ALP and impaired mineralization (Choi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%